Identifying and Rating Urogynecology Applications Using the APPLICATIONS Scoring System [4G]. Issue 5 (May 2017) - Wallace, Shannon; Mehta, Shailja; Farag, Sara; Kelley, Robert; Chen, Katherine
Abstract : INTRODUCTION: Thousands of medical applications (apps) are available for mobile devices. Finding accurate, provider-directed apps may be time-consuming and frustrating for urogynecologists. This study's objective is to identify and rate urogynecology (urogyn) apps using an adapted APPLICATIONS scoring system. METHODS: Urogyn apps were identified from the Apple iTunes and Google Play Stores using the following ten MESH terms: urogynecology, incontinence, prolapse, urinary tract infection, pelvic surgery, fecal incontinence, defecation disorder, voiding disorder, urethral diverticulum and fistula. Consumer-based and inaccurate apps were excluded. Remaining apps were rated with the APPLICATIONS scoring system, which uses objective and subjective criteria to evaluate comprehensiveness (the extent of ability to aid in clinical-decision making and to provide informational data). Objective rating components included price, paid subscription, literature used, in-app purchases, Internet connectivity, advertisements, text search field, interplatform compatibility and incorporated images, figures, videos and special features. Subjective rating components were ease of navigation and presentation. RESULTS: The urogyn-related MESH terms identified 137 and 238 apps in the Apple iTunes and Google Play stores, respectively. Only 8 apps (5 of which were in both stores) were found to be accurate and useful and were rated using the APPLICATIONS scoring system. The top rated apps were Practical Urology for Gynecologists and Practical Urology. CONCLUSION: Few accurate clinical-decision making and informational apps exist for urogynecologists. Apps varied by comprehensiveness and quality. This study highlights the importance of systematically reviewing and rating medical apps. It also emphasizes the need for developing accurate apps for urogynecologists that improve health provider performance and patient outcomes.